Sistem Keamanan pada Kendaraan Bermotor Roda Dua dengan Arduino dan Android berbasis Suara - Andreas Wijaya Kangnata; Agustinus Noertjahyana; Justinus Andjarwirawan (Jurnal Infra, 2021)
Along with the development of the number of motorcycle that are growing very fast and also the development of information and communication technology which is also high has brought benefits to the development of human civilization progress in the world and in Indonesia, especially smartphone, but problems related to crime, especially against motorcycle theft can also be said to be very high, so it is necessary to design a security system on motorcycle with Android and Arduino that can be commanded by voice.The system is created using an Android smartphone as a voice command input receiver and Arduino as a tool that controls hardware based on commands. This system will send voice commands from Android that have been converted into text with the speech to text method and send commands according to the command input via a message that sent via SMSManager to the SIM800L V2.0 module that installed on the Arduino Uno. Message received on the SIM800L V2.0 module will be processed by Arduino Uno, so that Arduino Uno can control each module installed, such as the buzzer, the GPS (Global Positioning System) module, and the relay as a controller of the security system, contact system, and starter system on motorcycle.Based on the results of the tests that have been carried out, it shows that this system can work properly to control motorcycle with Android and Arduino in providing a security system for motorcycle which is also equipped with a location feature to determine the location of the vehicle.